Optimalisasi Pemeriksaan Pajak Sehubungan dengan Dividen Konstruktif (Studi Kasus: KPP Madya Bekasi) - Banjarnahor, Jhonny M; Martani, Dwi (E-Jurnal Akuntansi, 2024)
This study aims to evaluate the tax imposition on constructive dividends in tax audits at Bekasi Medium Tax Office. DGT often make adjustments to transfer pricing transactions by imposing taxes on constructive dividends. However, some studies show that the imposition of tax on constructive dividends has the potential to cause double taxation and other problems. This study uses OECD evaluation criteria, namely relevance, coherence, effectiveness, efficiency, impact, and sustainability. This research is expected to be an additional reference for policy makers in making policies related to constructive dividends. This research was conducted using a qualitative case study method by triangulating the results of interviews with the documents and literature studies.  The result showed that in general the taxation of constructive dividend have met the OECD evaluation criteria. The criteria that fully met are effectiveness and sustainability. And the criteria that partially met are coherence and impact. This study suggests that clearer technical guidelines and more socialization are still needed so that the taxation of constructive dividends runs more optimally. Keywords: Constructive Dividend; Secondary adjustment; Tax Audit; Tax Avoidance; OECD Framework